2013
DOI: 10.1111/are.12320
|View full text |Cite
|
Sign up to set email alerts
|

Effects of dietary organic selenium on immune responses, total selenium accumulation and digestive system health of marron,Cherax cainii(Austin, 2002)

Abstract: A 90-day feeding trial was conducted to determine the effects of dietary organic selenium (OS) supplementation on immune responses, total selenium accumulation in various tissues and the digestive system health of marron Cherax cainii. A group of marron (initial weight 3.65 AE 0.05 g) were fed 0.2 g kg À1 of Sel-Plex â as a source of OS and were compared to a control group of marron that were not fed OS. After 90 days of feeding OS, total haemocyte counts (THC) and the percentages of granular and semigranular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 54 publications
2
10
0
Order By: Relevance
“…These results were consistent with those of previous studies [24,25]. It has been further demonstrated that Se is closely associated with many aspects of physiological function [26], and selenium deficiency facilitates inflammation.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…These results were consistent with those of previous studies [24,25]. It has been further demonstrated that Se is closely associated with many aspects of physiological function [26], and selenium deficiency facilitates inflammation.…”
Section: Discussionsupporting
confidence: 93%
“…Numerous studies have demonstrated that Se plays an important role in chemoprevention [2], neurobiology [3], aging [4], immune functions [5], muscle metabolism [6], redox reactions [7], inflammation [8], and many other aspects of health [9]. Se content has been closely associated with dietary Se in birds.…”
Section: Introductionmentioning
confidence: 99%
“…Antioxidant activity in abalone was significantly promoted by low to medium levels of dietary Se but decreased with high levels of dietary Se (Table ). This was consistent with the other findings for Nile tilapia (Lee et al, ), abalone (Wang et al, ), grouper (Lin & Shiau, ), cherry shrimp ( Neocaridina heteropoda ) (Broom, ), river shrimp (Kong et al, ) and marron ( Cherax cainii ) (Nugroho & Fotedar, ). There are a number of possible reasons why excess Se affects the antioxidant capacity of abalone.…”
Section: Discussionsupporting
confidence: 92%
“…It is of particular interest that fish fed deficient Se diet had a higher FCR compared to those fed normal Se diet; similar results were also observed in the studies of channel catfish (Wang and Lovell 1997), juvenile grouper (Lin and Shiau 2005) and grass carp(Cenopharyngodon idellus) (Su et al 2007). Su et al (2007) have reported adding Se to feeding diet enhanced the activities of amylase, protease and lipase enzymes, improved digestive system health and contributed to efficient digestion (Nugroho and Fotedar 2015). Although there was no significant difference of FCR between normal dietary Se treatment and excess dietary Se treatment but the juvenile olive flounder (Paralichthys olivaceus) and Acipenser fed high Se diets were observed the histopathological lesions of liver or kidney (Lee et al 2010;Riu et al 2014), owing to the damage of these important organs, a poorer feed efficiency for a long time might occur (Lee et al 2010).…”
Section: Discussionmentioning
confidence: 99%